Toward Value-Integrated Pedagogy: A Literature Review on Embedding Islamic Principles in EFL Teaching - Selvi, Selvi; Aisyah, Aisyah; Maida, Siti; Irma, Irma; Norliani, Norliani; Nengsih, Dora; Qamariah, Zaitun (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2025)
The integration of Islamic values into English as a Foreign Language (EFL) instruction has gained renewed attention in recent years, particularly as educators seek approaches that balance global communicative competence with moral and spiritual development. This study employs a qualitative narrative library research design to analyse scholarly works published between 2020 and 2025 that address the incorporation of Islamic principles within EFL curriculum and pedagogy. The reviewed literature reveals three overarching themes: (1) the philosophical foundations of Islamic education, which emphasize the inseparability of knowledge, adab, and ethical formation; (2) emerging pedagogical efforts to embed Islamic values through discourse, material selection, classroom interaction, and digital media; and (3) persistent gaps in curriculum-level frameworks, as most studies remain focused on teacher practices rather than systematic institutional design. Findings indicate that value-integrated EFL instruction is conceptually robust and pedagogically feasible. Yet, its implementation remains fragmented due to limited teacher preparation, insufficient instructional resources, and the absence of coherent curricular models. This study concludes that developing structured, context-sensitive frameworks is essential for ensuring that EFL curricula harmonize linguistic objectives with Islamic moral orientations. Implications are offered for curriculum developers, educators, and institutions seeking to create value-integrated EFL programs that support both communicative proficiency and ethical character formation.